Meta-Analysis of Lowering LDL Cholesterol and its Impact on the Cardiovascular System - Samson S. Badalyan, Syune V. Markosyan, Hajra Tariq, Zeeshan Malik, Andleeb Asghar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: By lowering LDL cholesterol levels, the risk of coronary heart disease (CHD) and other serious vascular events can be significantly reduced. In order to prevent cardiovascular illnesses (CVD), mainly coronary heart disease, LDL-cholesterol (LDL-C) levels must be tightly controlled on both a primary and secondary level (CHD). Despite the fact that patients in primary prevention experience a higher absolute number of atherosclerotic cardiovascular (CV) events than those in secondary prevention of CVD, subjects in primary prevention frequently receive little attention when it comes to the clinical management of LDL-C levels. Aim: To summarise the research supporting LDL cholesterol reduction treatments for elderly people. Method: For this meta-analysis, we searched PubMed, GOOGLE SCHOLAR, SCI.HUB, MEDLINE, and Embase for publications released between January 1, 2017, and December 28, 2021. As recommended by the 2018 American Academy of Cardiology and American Heart Association guidelines, randomised controlled trials evaluating cardiovascular outcomes of an LDL cholesterol-lowering medicine with a median follow-up of at least 2 years and data on older patients (aged 75 years).The search for literature source was limited to randomized controlled trials (human being). This meta-analysis, comprised of 24 trials from the Cholesterol Therapy Trialists' Collaboration meta-analysis plus five other trials, used data from six journals. 21492 (8%) of the 244090 participants in 29 studies, were over the age of 75. Among them, 11750 (54%) came from statin trials, 6209 (28%) from ezetimibe trials, and 3533 (16%) from PCSK9 inhibitor trials. We conducted network meta-analyses for the statins and non statin treatments. Results: Of the 244090 participants in 29 studies, 21492(8%) were over 75. These included 3533 (16%) from PCSK9 inhibitor studies, 11750 (54%) from statin trials, and 6209 (28%) from ezetimibe trials. A median follow-up period of 2 to 6 years was used. Without statistically differentiating from the risk reduction in patients under the age of 75 (085 [078-092]; pinteraction=037), LDL cholesterol lowering significantly reduced the risk of major vascular events (n=3519) by 26% for 1 mmol/L reduction in LDL cholesterol (RR 074 [95% CI 061-089]; p=00019).In older patients, there was no statistically significant difference in the RRs for statin (0.82 [0.73-0.91] and non-statin (0.67 [0.47-0.95]; pinteraction=0.64) treatment. Reduced LDL cholesterol in older persons was shown to benefit all components of the composite, including coronary revascularization (080 [066-096], stroke (073 [061-087], and myocardial infarction (080 [071-090]. Practical implication: This meta analysis can be used to improve the treatment of people withlowering LDL cholesterol. Conclusion: The viability and security of diminishing LDL cholesterol in more seasoned adults are now supported by further research provided by this meta-analysis. By non-statin and statin LDL cholesterol-bringing down medication, we identified a risk reduction for major vascular events that were at least as effective as that observed in younger patients Keywords: LDL, Meta-analysis, Cardiovascular, Cholesterol,Atherosclerosis, Primary and secondary prevention.